2021
DOI: 10.4037/ajcc2021187
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurse Burnout in Veterans Health Administration: Relation to Clinician and Patient Outcomes

Abstract: Background Critical care nurses have a burnout rate among the highest of any nursing field. Nurse burnout may impact care quality. Few studies have considered how temporal patterns may influence outcomes. Objective To test a longitudinal model of burnout clusters and associations with patient and clinician outcomes. Methods An observational study analyzed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In a longitudinal cohort study, ICU healthcare professionals demonstrated a change in self‐reported burnout symptoms from 23% before the COVID‐19 pandemic (October–December 2019) to 36.1% (May–June 2020) during the peak of the pandemic 3 . Burnout is not only damaging to clinicians, but studies also suggest burnout negatively impacts the delivery of care, patient outcomes, and nurse satisfaction 5,16–19 . Consequently, it is imperative to understand and prevent occupational burnout in critical care settings to protect both critically ill patients and those entrusted with providing their care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longitudinal cohort study, ICU healthcare professionals demonstrated a change in self‐reported burnout symptoms from 23% before the COVID‐19 pandemic (October–December 2019) to 36.1% (May–June 2020) during the peak of the pandemic 3 . Burnout is not only damaging to clinicians, but studies also suggest burnout negatively impacts the delivery of care, patient outcomes, and nurse satisfaction 5,16–19 . Consequently, it is imperative to understand and prevent occupational burnout in critical care settings to protect both critically ill patients and those entrusted with providing their care.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Burnout is not only damaging to clinicians, but studies also suggest burnout negatively impacts the delivery of care, patient outcomes, and nurse satisfaction. 5 , 16 , 17 , 18 , 19 Consequently, it is imperative to understand and prevent occupational burnout in critical care settings to protect both critically ill patients and those entrusted with providing their care.…”
Section: Introductionmentioning
confidence: 99%
“…However, most nursing burnout studies have been completed in other nursing subspecialty areas, like critical care and the emergency department (ED). [1,3,4] This mixed-methods research aimed to analyze MS nursing perspectives on burnout and STS. The research questions are: (1) What are perceived levels of burnout and STS in medical-surgical nurses?…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal bivariate analysis of Veteran Affairs (VA) Critical Care facilities indicates that high-burnout levels correlate to longer patient stays, high employee turnover intention, and lower employee satisfaction. [3] Shah and colleagues completed a cross-sectional data analysis on a sample of over 50,000 nurses in the United States. [7] The nurses who left their job within the model reported burnout at a staggering 31.5%.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Nurses identified stress and burnout as salient occupational concerns before the pandemic, 2 and the World Health Organization 3 classified burnout as an occupational phenomenon rather than a medical condition in 2019. During a 5-year longitudinal study conducted from 2013 through 2017, Mohr et al 4 identified that most Veterans Administration staff nurses described their burnout as moderate. Reported burnout correlated with increased patient intensive care unit (ICU) length of stay and lower reported employee morale.…”
mentioning
confidence: 99%